Investigations on VELVET regulatory mutants confirm the role of host tissue acidification and secretion of proteins in the pathogenesis of Botrytis cinerea. Issue 3 (23rd May 2018) - Müller, Nathalie; Leroch, Michaela; Schumacher, Julia; Zimmer, David; Könnel, Anne; Klug, Klaus; Leisen, Thomas; Scheuring, David; Sommer, Frederik; Mühlhaus, Timo; Schroda, Michael; Hahn, Matthias
Summary: The Botrytis cinere a VELVET complex regulates light‐dependent development and virulence. The goal of this study was to identify common virulence defects of several VELVET mutants and to reveal their molecular basis. Growth, differentiation, physiology, gene expression and infection of fungal strains were analyzed, and quantitative comparisons of in planta transcriptomes and secretomes were performed. VELVET mutants showed reduced release of citric acid, the major acid secreted by the wild‐type, whereas no significant role for oxalic acid was observed. Furthermore, a common set of infection‐related and secreted proteins was strongly underexpressed in the mutants. Quantitative secretome analysis with 15 N metabolic labeling revealed a correlation of changes in protein and mRNA levels between wild‐type and mutants, indicating that transcript levels determine the abundance of secreted proteins. Infection sites kept at low pH partially restored lesion expansion and expression of virulence genes by the mutants. Drastic downregulation of proteases in the mutants was correlated with incomplete degradation of cellular host proteins at the infection site, but no evidence was obtained that aspartyl proteases are required for lesion formation. The B. cinerea VELVET complex controls pathogenic differentiation by regulating organic acid secretion, host tissue acidification, gene expression and protein secretion.